American Catholic bishops and the politics of scandal: rhetoric of authority - O'Keefe, Meaghan (Routledge studies in religion, 2019)
Controlling consciences -- Citation and authority -- Human rights and the image of God -- Racism, abortion, and intrinsic evil -- The nuns on the bus -- Sounding authoritative.